KURIKULUM SEKOLAH DASAR (SD), SEKOLAH DASAR ISLAM TERPADU (SDIT), DAN MADRASAH IBTIDAIYAH (MI) - Iza Ananta; Maya; Nova Maratusoliha; Yunita Istina (NETIZEN: JOURNAL OF SOCIETY AND BUSSINESS, 2023)
This curriculum development model is used to develop a curriculum, where curriculum development is needed to improve or perfect the curriculum that was created to be developed by the central government, regional government or school, so that the curriculum in SD, SDIT, and MI has several differences in its implementation. The teaching profession in learning cannot be separated from changing students' behavior in a positive direction and teaching positive values ​​to children, it is also inseparable from being a professional teacher.